Tendencias investigativas en territorio y su importancia en la formación de profesionales (2015)
This essay derives four trends from previous research: (a) territory as the field of legal and political power, (b) territory as environment, (c) territory as a social construct, and (d) territory as physical space. In each trend, the positions of researchers is summarized, making this publication a source for all those who, driven by professional interest or investigative curiosity, wish to do research related to the territory as a field of study.